The Jewish women prisoners of Ravensbrück : who were they ? - Agassi, Judith B., 1924-2018 1924-2018 (Oneworld, 2007)
"This is the story of a nearly forgotten chapter of the Holocaust - of over 16,000 Jewish women, girls and children, their origins, itineraries and fates, who suffered in the horrendous Nazi concentration camp for women, Ravensbruck. As a historian, Judith Buber Agassi was struck by the changing conditions, countries of origin, and fates of these women during 5 distinct periods during the 6 years of the camp's existence. As a sociologist, she studied the social relations of the Jewish prisoners among themselves as well as with the non-Jewish majority." "After the mass murder of Jewish prisoners early in 1942, a larger group organization became impossible, but the Jewish women developed a special and effective form of small-group organization, the so-called camp-families. As a sociologist of gender, she surveyed the educational background and patterns of behavior specific to Jewish women, and has produced an impressive study."--BOOK JACKET.